A cancer stem cell associated gene signature for predicting overall survival of hepatocellular carcinoma - Liang, Xin-Yi; Zhang, Yue; He, Ya-Nan; Liu, Xue-Yi; Ding, Zhi-Hao; Zhang, Xiao-Dong; Dong, Ming-You; Du, Run-Lei (Frontiers in Genetics, 2022)
Hepatocellular carcinoma (HCC) is the most prevalent type of primary liver cancer characterized by high mortality and morbidity rate. The lack of effective treatments and the high frequency of recurrence lead to poor prognosis of patients with HCC. Therefore, it is important to investigate new HCC prognostic prediction tools for clinical application. Recent studies have shown that cancer stem cells (CSC) play essential roles in HCC progression. The aim of this study was to explore the prognostic value of CSC-related genes and establish a prediction model based on data from The Cancer Genome Atlas (TCGA) database. In this study, 475 CSC-related genes were obtained from the Molecular Signature Database and 160 differentially expressed CSC-related genes were identified using the limma R package in HCC patients in the TCGA database. A total of 79 CSC-related genes were found to be associated with overall survival (OS). Using the least absolute shrinkage and selection operator (LASSO) and multivariate Cox regressions, a 3-gene signature (RAB10, TCOF1 and PSMD14) was constructed. Receiver operating characteristic (ROC) curves and Kaplan-Meier survival curves were constructed to test the predictive value of the signature. Performance of the signature was validated using the International Cancer Genome Consortium (ICGC) dataset. In addition, immune feature and functional enrichment analyses were carried out to explore the underlying mechanisms. Moreover, a co-expression network was constructed through the weighted gene correlation network analysis (WGCNA) method in the TCGA dataset to select genes significantly associated with risk scores in HCC. Besides, the SGO2 gene was found significantly associated with risk scores and play an oncogenic role in HCC, and in vitro experiments revealed that it can promote HCC cell proliferation. Therefore, SGO2 may be a potential therapeutic target for HCC treatment. Finally, we constructed a nomogram to help clinicians make decisions about HCC treatment.